2020
DOI: 10.1016/j.tox.2019.152345
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic profile analysis of brain inferior colliculus following acute hydrogen sulfide exposure

Abstract: Highlights Transcriptomic profiling analyses following acute exposure to H 2 S were performed  Multiple signaling pathways were dysregulated following H 2 S exposure  PI3K/Akt and MAPK signaling pathways were activated after H 2 S exposure  MRI scan analysis revealed lesions in the IC and TH following H 2 S exposure  Acute H 2 S exposure induced a neuroinflammatory response

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 46 publications
3
28
0
Order By: Relevance
“…Continuous variables were expressed as mean ± SD, and differences between two groups were compared using Student’s t-test for normally distributed variables and Mann–Whitney U test for abnormally distributed variables. Differential expression analysis was performed with the cut-off thresholds of P < 0.05 and |log 2 FC| > 0.58 or |FC| > 1.5, which was consistent with previously reported methods [ 36 , 37 ]. For each study, P < 0.05 was considered as a significant difference.…”
Section: Methodsmentioning
confidence: 73%
See 1 more Smart Citation
“…Continuous variables were expressed as mean ± SD, and differences between two groups were compared using Student’s t-test for normally distributed variables and Mann–Whitney U test for abnormally distributed variables. Differential expression analysis was performed with the cut-off thresholds of P < 0.05 and |log 2 FC| > 0.58 or |FC| > 1.5, which was consistent with previously reported methods [ 36 , 37 ]. For each study, P < 0.05 was considered as a significant difference.…”
Section: Methodsmentioning
confidence: 73%
“…Using R’s “ limma (v3.42.2) ” package to identify differential expressed mRNAs (DEmRNAs) and lncRNAs (DElncRNAs) between IS and control samples. The P < 0.05, |log 2 fold change (FC)| > 0.58 or |FC| > 1.5 were selected as the cut-off thresholds, in accordance with previously reported methods [ 36 , 37 ]. Among DEmRNAs, we took the DEmRNAs that were overlapped with the ferroptosis-related genes as the differentially expressed ferroptosis-related genes (DEFRGs).…”
Section: Methodsmentioning
confidence: 99%
“…There are more than one thousand annual reports related to severe H 2 S exposure in the Unites States alone (ATSDR, 2016). However, the clear mechanisms of H 2 S-induced multiple organs toxicity have not been elucidated yet, which has delayed the development of suitable countermeasures for treatment after an H 2 S intoxication (ATSDR, 2016;Kim et al, 2018;Kim et al, 2020). Existing animal experiments such as those performed with anesthetized mice in an H 2 S inhalation exposure model or with rats that were intraperitoneally injected with sodium hydrosulfide (NaHS) do not faithfully reflect the common route of exposure in humans (Jiang et al, 2016;Sonobe et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Seizure activity has a high correlation with loss of consciousness in H2Sexposed mice (Anantharam et al 2017a). The frequency and severity of seizure activity varies among mice, although seizure severity predicts shorter survival time (Anantharam et al 2018;Anantharam et al 2017a;Kim et al 2018;Kim et al 2019). Interestingly, preventing seizures with an anti-convulsant agent prolongs the survival of mice during H2S exposure .Victims of acute H2S poisoning also develop pulmonary edema (Tanaka et al 1999) and heart failure (Sastre et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It is widely reported that H2S inhibits cytochrome c oxidase enzyme in mitochondria, however, this alone does not explain the broad spectrum of toxic effects from knockdown and coma, to development of vegetative states (Anantharam et al 2018;Anantharam et al 2017a;Anantharam et al 2017b;Guidotti 2015;Kim et al 2018;Kim et al 2019;Ng et al 2019;Snyder et al 1995;Tvedt et al 1991a;Tvedt et al 1991b). Transcriptomic and proteomic studies of the inferior colliculus in H2S-exposed mice showed that H2S induces dysregulation of multiple biological pathways including calcium homeostasis, oxidative stress, immune response, and neurotransmitters (Kim et al 2018;Kim et al 2019).…”
Section: Introductionmentioning
confidence: 99%